2024
DOI: 10.1088/1674-4527/ad0d5c
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA-QUARKS Survey. I. Survey Description and Data Reduction

Xunchuan 训川 Liu 刘,
Tie Liu,
Lei Zhu
et al.

Abstract: This paper presents an overview of the QUARKS survey, which stands for 'Querying Underlying mechanisms of massive star formation with ALMA-Resolved gas Kinematics and Structures'. The QUARKS survey is observing 139 massive gas clumps covered by 156 pointings at ALMA Band 6 (λ~1.3 mm). In conjunction with data obtained from the ALMA-ATOMS survey at Band 3 (λ~3 mm), QUARKS aims to carry out an unbiased statistical investigation of massive star formation process within protoclusters down to a scale of 1000 au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The targeted lines included, but were not limited to: (1) outflow tracers (e.g., CO, 13 CO, SiO, SO, H 2 CO); (2) cold gas tracer (N 2 D + ); (3) dense core and filament tracers (e.g., C 18 O, HC 3 N); (4) hot core tracers (e.g., CH 3 OH, C 2 H 5 CN, NH 2 CHO, CH 3 CN); (5) ionized-gas/HII-region tracer (H 30 α). The basics of the main targeted lines are summarized in Table 2 of Liu et al (2023b).…”
Section: Observing Strategymentioning
confidence: 99%
See 4 more Smart Citations
“…The targeted lines included, but were not limited to: (1) outflow tracers (e.g., CO, 13 CO, SiO, SO, H 2 CO); (2) cold gas tracer (N 2 D + ); (3) dense core and filament tracers (e.g., C 18 O, HC 3 N); (4) hot core tracers (e.g., CH 3 OH, C 2 H 5 CN, NH 2 CHO, CH 3 CN); (5) ionized-gas/HII-region tracer (H 30 α). The basics of the main targeted lines are summarized in Table 2 of Liu et al (2023b).…”
Section: Observing Strategymentioning
confidence: 99%
“…Line emission channels were flagged to obtain the continuum and spectral lines simultaneously. Liu et al (2023b) identified all the transitions of strong lines within the four SPWs by matching the reduced data cubes of the ALMA pipeline and the laboratory databases for the spectral lines (CDMS; Müller et al 2001). The QUARKS team generated a model spectrum as a mask for line emission channels.…”
Section: Data Calibration and Imagingmentioning
confidence: 99%
See 3 more Smart Citations